2015
DOI: 10.5603/cj.a2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients hospitalized for congestive heart failure with left ventricular ejection fraction ≥ 40%

Abstract: (Cardiol J 2015; 22, 4: 382-390)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…According to BARDICHE-index authors lower SBP was associated with higher HF exacerbation rate independently of LVEF [29]. Several authors have demonstrated that higher SBP was independently related to improved cardiovascular survival in patients with CHF [13,21,24,30]. Surprisingly, this study did not confirm the relationship between SBP and MACE in the whole group of patients or in study subgroups.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…According to BARDICHE-index authors lower SBP was associated with higher HF exacerbation rate independently of LVEF [29]. Several authors have demonstrated that higher SBP was independently related to improved cardiovascular survival in patients with CHF [13,21,24,30]. Surprisingly, this study did not confirm the relationship between SBP and MACE in the whole group of patients or in study subgroups.…”
Section: Discussioncontrasting
confidence: 70%
“…Some authors have suggested that low daytime BP variability may also influence prognosis in patients with HF [23]. Sherazi et al [24] and revealed that the absence of hypertension, as well as elevated urea and lower LVEF ≤ 45% indicate increased risk of short and long-term mortality. The relationship between DBP and MACE has been discussed in other publications concerning this subject [8,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The role of chronic heart ischemia as the cause of HFPEF was confirmed in other clinical studies even without concomitant impaired contractility. 8 In our study, CAD was an independent predictor of HFPEF.…”
supporting
confidence: 53%
“…Continuous variables were first evaluated for normal coronary artery disease (CAD), hypertrophic cardiomyopathy, congenital heart defects associated with ventricular hypertrophy, and diabetes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] According to the European Society of Cardiology (ESC), the diagnosis of HFPEF requires 4 criteria to be met: the presence of signs and symptoms typical of HF, normal or only mildly reduced LVEF, no LV dilation, and relevant structural heart disease or left ventricular diastolic dysfunction (or both).…”
mentioning
confidence: 99%
“…In normal or small LV, owing to increased passive stiffness of the LV, significant changes in pressure may be seen even with little or no detectable change in ventricular volume. [12] As Sherazi et al [13] reported, a smaller cavity in heart failure with preserved LV EF increased passive chamber stiffness. The small LV cannot accept venous return adequately, and such high LV filling pressure may worsen the symptoms of heart failure and lead to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%